Clarks brings digital touch to traditional shoemaking - Authers, Ross (Engineering cases, 2012)
Thanks to 3D CAD software and 3D printers, Clarks has moved from hand-drawn sketches and factory-manufactured samples to creating prototypes in a digital world, decreasing costs and improving its time-to-market agility.